Effect of Water Stress on the Growth and Yield of Rhodes Grass (Chloris Gayana. L. Kunth.) - Arshad, Imran; Ali, Wajiha; Khan, Zaheer Ahmed; Bhayo, Waqar Ahmed (PSM Biological Research, 2016)
Efficient irrigation is an important aspect to get good quality fodder. By keeping this fact in view a field experiment was conducted at Siddique Farm, Tando Adam, Sindh-Pakistan, to investigate the effect of water stress on Rhodes Grass (Chloris gayana. L. Kunth.). The experiment was laid out in a randomized complete block design (RCBD) with three replications. Thus, the total number of plots was fifteen and the size of each plot was (16m x16m). The Rhodes grass (Fine-cut Variety) i.e. 10 kg/ acre was sown on (March 15, 2013) in the prepared land and Phosphorous fertilizer dose applied at sowing accordingly. The watering treatments comprised of five irrigation watering treatments (5, 10, 15, 20 and 25 days) (I1, I2, I3, I4 and I5 respectively). Nitrogen was applied in split doses by broadcasting. The results revealed that I2 showed high yielding results for all the agronomic parameters i.e. maximum plant height (125.38 cm), tillers / plant (4.86), leaves / tillers (10.13), leaf area (307.05 cm2), green fodder yield (22.35 ton/ha/cut), and crude protein content (9.77) respectively. I2 also produced highest (6.41 ton/ha/cut) dry fodder yield per hectare per cut. Too early or late watering reduced the yield and yield parameters of Rhodes grass. However, further investigations are necessary to establish the present findings in other regions of Pakistan as the seed variety (Fine-cut) was used in this study therefore; results may vary for other type of seed varieties.